Some additional data to the genus Bombax L. (Malvaceae- Bombacoideae) for the flora of Vietnam - Loc, Phan Ke; Nhung, Nguyen Thi; Duyen, Nguyen Thi Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4, 2017)
Some additional data to the genus Bombax L. (Malvaceae- Bombacoideae) for the flora of Vietnam   Phan Kế Lộc 1 , Nguyễn Thị Nhung 2 , Nguyễn Thị Ánh Duyên 3 1 Faculty of Biology, VNU University of Science, 334 Nguyễn Trãi, Thanh Xuân, Hanoi, Vietnam 2 VNU University of Education, 144 Xuân Thủy, Cầu Giấy, Hanoi, Vietnam   Abstract: Bombax L. (Malvaceae- Bombacoideae) is a small genus with 8 species, distributed in Old World. Up to now there are 4 species of Bombax registered for the flora of Vietnam, namely B. albidum Gagnep., B. anceps Pierre, B. ceiba L. and B. insigne Wall. Goal of this paper is to contribute some additional data of its species composition and distribution. Specimens of six collecting numbers (three of native and three of cultivated species) were collected, studied and housed at the herbarium (HNU) of the Hanoi University of Science, Vietnam National University. Due to the lacking of branchlets bearing leaves and flowers of collected specimen P 7660 is named as Bombax cf. cambodiense Pierre, new occurrence for the flora. Bombax anceps Pierre for the first time was seen and taken photos in northwestern Son La Province, far from the main locations in the south. Morphological characters mainly of abaxial face calyx, petals, stamens and pistil of cultivated Bombax ceiba L. are illustrated. The occurrence of Bombax insigne Wall. is not confirmed by herbarium specimens. Comparaison of main morphological characteristics of studied Bombax taxa are presented.